Molecules and Mechanisms Implicated in the Peculiar Antigenic Activation Process of Human Vγ9Vδ2 T Cells - Harly, Christelle; Peigné, Cassie-Marie; Scotet, Emmanuel (Frontiers in Immunology, 2015)
In humans, as well as in most non-human primates, the major peripheral γδ T cell subset, which accounts several percent of the whole lymphoid cells pool in adults, carries an heterodimeric TCR composed of Vγ9 and Vδ2 chains. Vγ9Vδ2 T cells are specifically and strongly activated by small organic pyrophosphate molecules termed phosphoantigens (phosphoAg). These low molecular weight compounds are metabolites that are produced by either microbes or endogenously, as intermediates of the mammalian mevalonate pathway, and can accumulate intracellularly during cell stress like transformation or infection. Despite the characterization of numerous natural and synthetic phosphoAg, the mechanism(s) underlying the unique and specific antigenic activation process induced by these compounds remains poorly understood. Activation is both TCR- and cell-to-cell contact-dependent, and results of previous studies have also strongly suggested a key contribution of membrane-associated molecules of primate origin expressed on target cells. The recent identification of B7-related butyrophilin (BTN) molecules CD277/BTN3A, and more precisely their BTN3A1 isoforms, as mandatory molecules in the phosphoAg-induced recognition of target cells by Vγ9Vδ2 T cells opens important opportunities for research and applications in this field. Here we review the unusual and complex antigenic reactivity of human Vγ9Vδ2 T cells. We highlight the recent advances in our understanding of this process, and propose a model that integrates the type I glycoprotein BTN3A1 and its intracellular B30.2 domain as a physical intermediate implicated in the detection of dysregulated intracellular levels of phosphoAg and the sensing of cell stress by Vγ9Vδ2T cells. A better understanding of this mechanism will help optimize novel immunotherapeutical approaches that utilize the unique functional potential of this major γδ T cell subset.